2012
DOI: 10.1073/pnas.1209979109
|View full text |Cite|
|
Sign up to set email alerts
|

Donor-dependent variations in hepatic differentiation from human-induced pluripotent stem cells

Abstract: Hepatocytes generated from human induced pluripotent stem cells (hiPSCs) are unprecedented resources for pharmaceuticals and cell therapy. However, the in vitro directed differentiation of human pluripotent stem cells into mature hepatocytes remains challenging. Little attention has so far been paid to variations among hiPSC lines in terms of their hepatic differentiation. In the current study, we developed an improved hepatic differentiation protocol and compared 28 hiPSC lines originated from various somatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
249
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 287 publications
(273 citation statements)
references
References 33 publications
20
249
3
1
Order By: Relevance
“…Previous studies suggested that reprogrammingassociated errors of retention of donor cell-specific epigenetic memory bias the differentiation potency of hiPSCs toward some lineages (Kim et al, 2010b(Kim et al, , 2011Polo et al, 2010). However, other studies did not confirm such correlations, or alternatively suggested that donor-specific genetic variability affecting lineage-primed gene expression might play a more dominant role (Ohi et al, 2011;Hu et al, 2011;Kajiwara et al, 2012;Kyttälä et al, 2016).…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies suggested that reprogrammingassociated errors of retention of donor cell-specific epigenetic memory bias the differentiation potency of hiPSCs toward some lineages (Kim et al, 2010b(Kim et al, , 2011Polo et al, 2010). However, other studies did not confirm such correlations, or alternatively suggested that donor-specific genetic variability affecting lineage-primed gene expression might play a more dominant role (Ohi et al, 2011;Hu et al, 2011;Kajiwara et al, 2012;Kyttälä et al, 2016).…”
Section: Introductionmentioning
confidence: 72%
“…EN differentiation. EN differentiation was performed as described previously, with slight modification 36 . The single-cell suspensions of human pluripotent stem cells were plated onto Matrigel-coated plates in RPMI1640 (Life Technologies) containing 2% B27, 100 ng ml À 1 Activin A, 3 mM CHIR99021 and 0.5% Pen/Strep.…”
Section: Methodsmentioning
confidence: 99%
“…The hiPSC technology could also contribute to production of rare types of erythrocytes-for example, D2, Fy(a2b2), Di(b2), and Jr(a2) [5]. However, it is well known that hiPSC clones are heterogeneous with respect to their differentiation potential [6]. Consequently, the ability to distinguish clones suitable for in vitro erythrocyte production from among identical donor-derived hiPSC clones is crucial.…”
Section: Introductionmentioning
confidence: 99%